Designated Inhospitality: The Treatment of Asylum Seekers Who Arrive by Boat in Canada and Australia - Taylor, Luke (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2015)
This paper argues that there are distinct parallels between changes to the Immigration and Refugee Protection Act enacted by Bill C-31 (2012), in particular the Designated Foreign National regime (DFN), and Australia’s treatment of asylum seekers who arrive by boat. It is contended that recent Australian history and policy demonstrate the perils of adopting an ideology of control and exclusion toward asylum seekers instead of a politics of hospitality, and that Australia’s present political climate provides a stark and salutary warning to Canada, as it follows a similar path of securitization. The paper first explains what is meant by a politics of hospitality. In Part I, it analyzes Australia’s attitude toward, and its treatment of, asylum seekers, focusing in particular on the period since 1989. It is argued that Australia’s inhospitable stance toward asylum seekers has had discernible negative outcomes that provide important lessons for Canada. Part II provides a brief historical overview of Canadian policy toward asylum seekers, followed by an analysis of the DFN regime with reference to international law. It then argues that the DFN provisions contravene the Canadian Charter of Rights and Freedoms. The paper concludes by suggesting that Canada is at risk of following Australia’s security-oriented, inhospitable stance toward asylum seekers.